Lifetime encyclopedia of letters - Meyer, Harold E. (Paramus, N.J. ; London : Prentice Hall, 1998)
How you will benefit from this book. Requesting favors. Declining requests. Sales. Fund raising. Collection. Information: providing and requesting. Complaints: making and answerring...
Keywords: Encyclopedia; Letter writing; Commercial correspondence; Letter writing; Commercial correspondence